A framework for designing and evaluating realistic blockchain-based local energy markets. (1st January 2021) - Christidis, Konstantinos; Sikeridis, Dimitrios; Wang, Yun; Devetsikiotis, Michael
Abstract: A growing customer base for solar-plus-storage at the grid edge has resulted in stronger interest at the regulatory level towards energy markets at the distribution level. Local energy markets (LEMs) running on blockchains are being studied as a possible direction, but the relevant literature treats the blockchain component as a black box. We make the case that this approach is flawed because the choices in this layer affect the market's performance significantly. We explicitly identify the design space that the blockchain layer introduces, and analyze how the design choices made therein affect the performance, governance, and degree of decentralization of these markets. As an exercise, we consider three distinct configurations for a next-generation LEM, and compare their performance on both the blockchain and the market layer via a case study. We demonstrate that simple changes in the data model can decrease the market efficiency by up to 90%. We also show that changes in the way bids get encrypted may result in economic improvements, but they do so at the risk of subverting the proper operation and resilience of the market. The simulations for our case study are conducted via a framework that we developed and open-sourced as part of this work. Highlights: The blockchain layer affects the market's efficiency and degree of decentralization. Design space in the blockchain layer is systematically and evaluated for trade-offs. Blockchain-based energy market is practically designed in detail from the ground-up. Case study compares three distinct blockchain-based energy market configurations. Numerical evaluation shows data model change decreasing the market efficiency by 90%.